2020
DOI: 10.3390/biom10091322
|View full text |Cite
|
Sign up to set email alerts
|

Lighting Conditions Influence the Dynamics of Protease Synthesis and Proteasomal Activity in the White Rot Fungus Cerrena unicolor

Abstract: Recent transcriptomic and biochemical studies have revealed that light influences the global gene expression profile and metabolism of the white-rot fungus Cerrena unicolor. Here, we aimed to reveal the involvement of proteases and ubiquitin-mediated proteolysis by the 26S proteasome in the response of this fungus to white, red, blue and green lighting conditions and darkness. The changes in the expression profile of C. unicolor genes putatively engaged in proteolysis were found to be unique and specific to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Environmental factors such as nutrients, temperature, carbon dioxide concentration, and light are crucial for the growth of mushroom-forming fungi. Specifically, light plays a significant role in regulating the growth, development, and metabolism of mushrooms as an environment signal, and factors such as light intensity and wavelength are particularly important. Therefore, providing proper light conditions is essential for the induction and development of fruiting bodies. The effect of light has been investigated in various mushrooms, including Coprinopsis cinerea, Inonotus rheades, Lentinula edodes, Pleurotus ostreatus, , Pleurotus eryngii, Cerrena unicolor, and Hypsizygus marmoreus. , Studies have shown that different light qualities have varying effects on the growth of mycelium and the development of primordia or fruiting bodies . For example, although most mushrooms do not require light during the mycelial growth stage, the mycelia of Cordyceps militaris exposed to white light exhibit significantly faster growth compared to those kept in the dark.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors such as nutrients, temperature, carbon dioxide concentration, and light are crucial for the growth of mushroom-forming fungi. Specifically, light plays a significant role in regulating the growth, development, and metabolism of mushrooms as an environment signal, and factors such as light intensity and wavelength are particularly important. Therefore, providing proper light conditions is essential for the induction and development of fruiting bodies. The effect of light has been investigated in various mushrooms, including Coprinopsis cinerea, Inonotus rheades, Lentinula edodes, Pleurotus ostreatus, , Pleurotus eryngii, Cerrena unicolor, and Hypsizygus marmoreus. , Studies have shown that different light qualities have varying effects on the growth of mycelium and the development of primordia or fruiting bodies . For example, although most mushrooms do not require light during the mycelial growth stage, the mycelia of Cordyceps militaris exposed to white light exhibit significantly faster growth compared to those kept in the dark.…”
Section: Introductionmentioning
confidence: 99%